Determinan Turnover Intention, Peran Mediasi Organizational Commitment dan Job Satisfaction Pada Karyawan Perusahaan Trading - Devy Christine; Elistia Elistia (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyse the effect of job security on turnover intention, with job satisfaction and organisational commitment acting as mediating variables, amongst employees of electrical trading and distribution companies in the JABODETABEK region. This study employs a quantitative approach using Structural Equation Modelling (SEM-PLS). The sample comprised 132 respondents selected using probability sampling via simple random sampling. Data were collected via a Likert-scale questionnaire and analysed using SmartPLS 4.0. The results indicate that job security has a significant negative effect on turnover intention. Furthermore, job security has a positive effect on job satisfaction and organisational commitment. Both of these variables were also found to have a negative effect on turnover intention. The results of the mediation analysis indicate that job satisfaction and organisational commitment significantly mediate the relationship between job security and turnover intention. These findings suggest that enhancing perceptions of job security can increase employee satisfaction and commitment, thereby reducing the intention to leave. This study implies that companies need to improve job stability in order to retain employees and enhance organisational performance sustainably.